1996
DOI: 10.1016/s0896-6273(00)80220-2
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Clock Neurons in the Silkmoth Antheraea pernyi: Novel Mechanisms of Period Protein Regulation

Abstract: We examined Period (PER) protein regulation in the brain of the silkmoth Antheraea pernyi. PER expression is restricted to the cytoplasm and axons of eight neurons, with no evidence of temporal movement into the nucleus. These neurons appear to be circadian clock cells, because PER and per mRNA are colocalized and their levels oscillate in these cells, Timeless protein immunoreactivity is coexpressed in each PER-positive neuron, and clock protein and mRNA oscillations are all suppressed in these neurons by con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
193
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(210 citation statements)
references
References 35 publications
16
193
1
Order By: Relevance
“…First, the apPer promoter may not be functional in S2 or Sf9 cells, perhaps because essential activators or co-activators are absent in those cell lines. This possibility is supported by the extreme spatial restriction of apPER expression in silkmoth brain to only ϳ8 cells (15). Second, the apPer genomic fragments may contain a binding site for transcriptional repressors endogenously expressed in S2 and Sf9 cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the apPer promoter may not be functional in S2 or Sf9 cells, perhaps because essential activators or co-activators are absent in those cell lines. This possibility is supported by the extreme spatial restriction of apPER expression in silkmoth brain to only ϳ8 cells (15). Second, the apPer genomic fragments may contain a binding site for transcriptional repressors endogenously expressed in S2 and Sf9 cells.…”
Section: Resultsmentioning
confidence: 99%
“…6B). Such a feedback loop could explain the previously detected in vivo rhythms in apPer RNA and protein levels (15,26). However, it remains unclear why apPER is always primarily cytoplasmic in A. pernyi brain neurons, when it possesses an evolutionarily ancient, classic bipartite NLS (Fig.…”
Section: Figmentioning
confidence: 93%
See 1 more Smart Citation
“…These findings are different from Drosophila (Liu et al, 1988;Siwicki et al, 1988). Two possible reasons for the differences are that the translocation mechanism between cytoplasm and nucleus in Drosophlia is a unique mechanism Archives of Insect Biochemistry and Physiology August 2008 (Sauman and Reppert, 1996) or the anti-PER may not bind with all forms of PER protein Zavodaska et al, 2005).…”
Section: Interactions Among Per Pdf and Crzmentioning
confidence: 99%
“…1; see review Žitňan and Adams, 2005) and corazonin immunoreactivity was detected in brain lateral neurosecretory cells in representatives of most major insect orders, except beetles (Veenstra and Davis, 1993;Cantera et al, 1994;Hansen et al, 2001;Roller et al, 2003). In moths these corazonin lateral cells also express the circadian clock protein period (PER) involved in the regulation of circadian rhythms (Sauman and Reppert, 1996;Wise et al, 2002). Connection between circadian rhythms and ecdysis is indicated by extirpation manipulations, which showed that these cells may be important for photoperiod-dependent induction of diapause occurring after pupal ecdysis (Shiga et al, 2003).…”
Section: Roles Of Neuropeptides In Eth Release Corazonin and Its Recementioning
confidence: 99%